2021
DOI: 10.9789/2175-5361.rpcfo.v13.9403
|View full text |Cite
|
Sign up to set email alerts
|

Xerostomia and breast cancer / Xerostomia e câncer de mama

Abstract: Objetivo: identificar os estudos que descrevem a prevalência de xerostomia em pacientes com câncer de mama e em quimioterapia. Método: revisão integrativa, partindo da questão norteadora << Quais as evidências científicas sobre a prevalência de xerostomia em pacientes com câncer de mama e em quimioterapia? >>. Foi realizada uma busca nas bases de dados PubMed, LILACS e SciELO por meio dos Descritores em Ciências da Saúde. Foram encontrados 63 artigos, que foram analisados por dois pesquisadores seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…In this study, the patients only used chemotherapy drugs (cyclophosphamide, epirubicin, and docetaxel) and did not have other diseases besides cancer. Pinto et al demonstrated that breast cancer patients undergoing adjuvant chemotherapy with CEF or CMF (cyclophosphamide, epirubicin, or methotrexate, 5uorouracil) showed reduced salivary ow rates during and after chemotherapy [30], supporting our ndings. Additionally, it is important to note that salivary ow can also be associated with other factors such as age, ethnicity, other diseases, or syndromes like Sjogren's.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the patients only used chemotherapy drugs (cyclophosphamide, epirubicin, and docetaxel) and did not have other diseases besides cancer. Pinto et al demonstrated that breast cancer patients undergoing adjuvant chemotherapy with CEF or CMF (cyclophosphamide, epirubicin, or methotrexate, 5uorouracil) showed reduced salivary ow rates during and after chemotherapy [30], supporting our ndings. Additionally, it is important to note that salivary ow can also be associated with other factors such as age, ethnicity, other diseases, or syndromes like Sjogren's.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, it is important to note that salivary ow can also be associated with other factors such as age, ethnicity, other diseases, or syndromes like Sjogren's. Therefore, continuous monitoring of salivary ow and a thorough medical history are relevant during oncological treatment [30].…”
Section: Discussionmentioning
confidence: 99%